Academic Procrastination in High School Students: An Exploratory Study - Rshaid, Abdullah M. Bani; M. Jaradat, Abdul-Kareem (Journal of Posthumanism, 2025)
Academic procrastination is a common phenomenon among school students that affects their academic performance and mental health. This study explored correlations between academic procrastination, test anxiety, academic achievement and satisfaction with study among high school students. The sample consisted of 480 students (mean age was 17.02 years) selected from four high schools in Jordan. The variables of the study were measured using an academic procrastination scale, a test anxiety scale, a single-item question for assessment of satisfaction with study, and GPA as a measure of academic achievement. The results revealed that procrastination positively and significantly correlated with test anxiety. Additionally, there were negative and significant correlations between procrastination and each of academic achievement and satisfaction with study. Likewise, there were negative and significant correlations between test anxiety and each of academic achievement and satisfaction with study. On the other hand, academic achievement positively and significantly correlated with satisfaction with study. Based on the results of this study, school counselors should help procrastinating students manage their time effectively, so that they get better academic results and reduce their test anxiety.